AI-Enhanced Criminal Investigations and Ḥudūd Offenses: A Sharīʿah Compliance Framework - Muhammad Jibril, Abubakar; Abdulmudallib Bello, Rabiu; Abubakar, Abbas (Alauddin Law Development Journal (ALDEV), 2025)
The article examines the interface of Islamic law and emerging AI technology in criminal investigation. It takes the legal normative doctrinal approach to examine predictive policing and facial recognition against Qurʾānic evidentiary and confessionary requirements. The analysis identifies a fundamental doctrinal tension: machine-generated evidence cannot substitute for the traditional proof Sharīʿah requires. A hybrid model is proposed on the grounds of maqāṣid al-Sharīʿah, granting artificial intelligence secondary, not primary, evidence status. Safeguards include judicial oversight, open algorithms, accountability, enforcement of data protection law, and an outright prohibition on AI input where uncertainty persists. The model operates within Islamic legal doctrine, conforming to technological advancement while upholding the Qurʾān's overarching commitment to justice. The study illustrates that the ethical frameworks underlying the development and deployment of AI can be consonant with Islamic teaching, specifically the values of justice and common good in the Qurʾān and related jurisprudence.